Utilization of maternal and child health services in Enugu, South East, Nigeria - Okpala, Pat U.; Okoye, Chinwendu L.; Adeyemo, Florence O.; Iheanacho, Peace N.; Emesonwu, Anthonia C.; Osuala, Eunice O.; Okpala, Ikenna G. (International Journal Of Community Medicine And Public Health, 2019)
Background: Nigeria continues to have one of the highest rates of maternal mortality in the world at 814 deaths per 100,000 live births despite several efforts. Various factors can influence appropriate utilization of services during pregnancy, childbirth and postpartum. This study examined the perceived factors that influence the utilization of maternal and child-health services among mothers in Enugu, South-East Nigeria. Methods: A descriptive survey design was adopted for the study. The study population of 323 pregnant women was determined using the Power Analysis formula. The instrument used for data collection was a self-developed questionnaire. Demographic information of the women was also obtained for the study. The analysis was done with the software statistical package for Social Sciences (SPSS) Version 16.0. Study period was from April 2016 to August 2016. Results: There was high antenatal clinic attendance (93.1%) and utilization of postnatal care services (93.1%). Also, the major factors that influenced the utilization of maternal and child health services were professionally defined needs, accessibility of health care services and economic status. Conclusions: There was high utilization of maternal and child health care services which was influenced by some factors. There is a need for nurses and other health workers to be actively engaged in educating mothers during antenatal visits. Sustainable financial subsidies and community-based initiatives should be developed to encourage early antenatal clinic visits and to provide the necessary information on the importance of facility-based antenatal and postnatal care.